IMPLEMENTATION OF THE PRINCIPLES OF SIMPLE, FAST, AND LOW-COST JUSTICE IN THE ELECTRONIC JUSTICE SYSTEM: NORMATIVE STUDY OF THE EFFECTIVENESS OF INFORMATION TECHNOLOGY IN THE JUDICIAL PROCESS - Pakaya, Renly Aprilia (DE'RECHTSSTAAT, 2024)
This study aims to analyze the implementation of the principle of simple, fast, and low-cost justice through the implementation of the Electronic Justice System (e-Justice) in Indonesia, as well as the effectiveness of information technology in supporting a modern justice system. The research method used is a normative approach by examining various laws and regulations, such as Law Number 48 of 2009 concerning Judicial Power and Law Number 27 of 2022 concerning Personal Data Protection. The results of the study show that e-Justice has increased the efficiency of the judicial process through the digitization of case administration, accelerating legal procedures, and reducing costs that previously burdened the community. This system also expands public access to judicial services, especially for those in remote areas. However, its implementation still faces challenges such as limited technological infrastructure, low digital literacy among the community, and potential threats to data security and privacy. The conclusion of this study is that e-Justice is a progressive step in Indonesian judicial reform to realize the principle of simple, fast, and low-cost justice. However, further efforts are needed in equalizing infrastructure, digital literacy training, and improving cybersecurity systems to support more effective and inclusive implementation. With these steps, e-Justice can become a strategic tool to improve the quality of judicial services and substantive justice for all levels of society.